PEMBERDAYAAN BERBASIS MASJID : IMPLEMENTASI TEKNIK FGD DALAM MENINGKATKAN SEMANGAT BELAJAR AGAMA DI MDTA - -, Yulia Annisa; Azwar, Azwar (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article wants to examine the implementation of FGD techniques in mosque-based empowerment activities as an effort to increase the enthusiasm for learning Religion for At-Taubah MDTA students. This can be done to increase enthusiasm and participation for MDTA students by modifying learning methods by implementing FGD techniques so that learning is not monotonous and boring. The research method used is social participatory action research. This study found that FGD techniques that were implemented effectively could increase participation and increase enthusiasm for religious learning in students at MDTA At-Taubah through the stages; 1) the preparation stage consists of initial mapping, trust building, field preparation. 2) The stages of implementation consist of the orientation, exploration, transition and work and productivity stages of the FGD. The real results obtained were an increase in knowledge and insight in the field of religion, the application of good morals and manners, as well as increased skills in reading and writing the Koran as well as skills in carrying out religious practices.